2020
DOI: 10.1186/s12885-020-07233-1
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, single-arm, phase II clinical trial of intraoperative radiotherapy using a low-energy X-ray source for local advanced Laryngocarcinoma (ILAL): a study protocol

Abstract: Background: Laryngocarcinoma (LC), in most cases a squamous cell carcinoma, accounts for 1~5% of the incidence of all tumors. At present, laryngocarcinoma is mainly managed with the integration of surgery and radioand chemo-therapies. The current development trend of treatment is to improve the local control rate of tumor and the quality of life of patients. Intraoperative radiation therapy (IORT) is a radiotherapy that delivers single high dose irradiation at a close range to the tumor bed during the surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…One of the most prevalent forms of cancers of the head and neck is laryngeal cancer, and more than 95% of cases are laryngeal squamous cell carcinomas (LSCC) (Dong et al, 2020). One to five percent of all tumors are laryngeal cancers, & their mortality and morbidity are rising (Li et al, 2016;Yang et al, 2020). Hoarseness is a possible early symptom of LSCC, but it is not specific and is often ignored (Chen et al, 2019;Groome et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most prevalent forms of cancers of the head and neck is laryngeal cancer, and more than 95% of cases are laryngeal squamous cell carcinomas (LSCC) (Dong et al, 2020). One to five percent of all tumors are laryngeal cancers, & their mortality and morbidity are rising (Li et al, 2016;Yang et al, 2020). Hoarseness is a possible early symptom of LSCC, but it is not specific and is often ignored (Chen et al, 2019;Groome et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The most significant advantage of IORT is that it imparts a lower radiation hazard to other organs, such as the bowel. Recent studies have demonstrated that IORT is effective in treating breast cancer, 12 head and neck cancer 13 and thymoma. 14 However, IORT requires further exploration in liver cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the etiology of laryngeal cancer isn't clear, but it is possibly related to smoking, air pollution, drinking, endocrine disorders, etc. (5,6). At present, the treatment of laryngeal cancer mainly includes surgery, radiotherapy, chemotherapy, and laser therapy.…”
Section: Introductionmentioning
confidence: 99%